2010
DOI: 10.1186/1472-6947-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of the internet as a source of health information by Spanish adolescents

Abstract: BackgroundThe Internet is a fundamental part of the daily life of adolescents, they consider it as a safe and confidential source of information on health matters. The aims is to describe the experience of Spanish adolescents searching for health information on the Internet.MethodsA cross-sectional study of 811 school-age adolescents in Granada was carried out. An adapted and piloted questionnaire was used which was controlled by trained personnel. Sociodemographic and health variables were included together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 18 publications
4
37
0
7
Order By: Relevance
“…Teenagers are exposed to health warning messages accidentally, by change, when accessing certain Internet websites or when connecting to social networks. In this respect, the data of present research is similar to recent findings about adolescents health-seeking behaviours, especially in matters related to sexual diseases, physical exercises, nutrition and weight maintenance (Jiménez-Pernett et al, 2010, Gray et al, 2005, Skinner et al 2003. Searching on the Internet of certain medical terms and of health related topics is rather a response to factors that threaten the health condition, such as the presence of physical symptoms that are overwhelming or stressful.…”
Section: Discussion Limits and Conclusionsupporting
confidence: 79%
“…Teenagers are exposed to health warning messages accidentally, by change, when accessing certain Internet websites or when connecting to social networks. In this respect, the data of present research is similar to recent findings about adolescents health-seeking behaviours, especially in matters related to sexual diseases, physical exercises, nutrition and weight maintenance (Jiménez-Pernett et al, 2010, Gray et al, 2005, Skinner et al 2003. Searching on the Internet of certain medical terms and of health related topics is rather a response to factors that threaten the health condition, such as the presence of physical symptoms that are overwhelming or stressful.…”
Section: Discussion Limits and Conclusionsupporting
confidence: 79%
“…[26] Two cross-sectional studies were conducted to discover adolescents' experience with using the Internet to seek out (or gather) health information. One study, [27] investigated a Catholic adolescent group while Jiménez-Pernett, et al [1] investigated a sample of Spanish adolescents. Their results were consistent, as they found that most of the adolescents are satisfied and at ease with using the Internet to get health information about topics such as skin care, cosmetics, body image, diet habits, and exercise.…”
Section: Internet Use For Seeking Health Informationmentioning
confidence: 99%
“…The literature indicated that the most frequently searched topics for health care on the Internet among adolescents were diet habits, exercise, body image, cosmetics, and skin care. [1,27] A systematic review and meta-analysis of the effects of health interventions using the Internet on health behavioral changes included 85 studies with a total of 43,236 participants from different populations. The study revealed that interventions using the Internet do have a small but significant effect on physical activity, dietary behavior, and alcohol consumption.…”
Section: Attitude Toward Internet Use For Health Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all Internet users use it for health-related information searches. 5,12,[14][15][16][17] Some studies showed the most frequent electronic health-related information seekers are young and middle-aged Internet users, 5,14,17,18 people with higher education, 5,12,14,17-19 the middle to high income group, 12,20 females, 5,19,20 employed, 14 and patients with chronic diseases. 12,14,16,17,19 Our multivariate logistic regression model demonstrated electronic health informationseeking behavior in those who were female patients, having chronic disease, living as a couple, having e-health service experience, being a daily Internet user, and having a longer duration of Internet use per day.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%